Nature Prescriptions and Indigenous Peoples: A Qualitative Inquiry in the Northwest Territories, Canada - Redvers, N; Hartmann-Boyce, J; Tonkin-Crine, S (MDPI, 2024)
Nature prescription programs have become more common within healthcare settings. Despite the health benefits of being in nature, nature prescriptions within the context of Indigenous Peoples have received little attention. We therefore sought to answer the following question: What are circumpolar-based physicians’ and Indigenous Elders’ views on nature prescribing in the Northwest Territories, Canada? We carried out thirteen semi-structured interviews with physicians between May 2022 and March 2023, and one sharing circle with Indigenous Elders in February 2023. Separate reflexive thematic analysis was carried out to generate key themes through inductive coding of the data. The main themes identified from the physician interviews included the importance of cultural context; barriers with nature prescriptions in the region; and the potential for nature prescriptions in the North. Reflections shared by the Elders included the need for things to be done in the right way; the sentiment that the Land is not just an experience but a way of life; and the importance of traditional food as a connection with Nature. With expanding nature prescription programs, key considerations are needed when serving Indigenous communities. Further investigation is warranted to ensure that nature prescriptions are appropriate within a given context, are inclusive of supporting Land-based approaches to health and wellbeing, and are considered within the context of Indigenous self-determination.